2022
DOI: 10.1101/2022.04.07.22273446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of patient-specific cell free DNA assays for monitoring of minimal residual disease in solid tumors

Abstract: Real time monitoring of disease status is an essential part of cancer management. The low sensitivity and specificity of serum markers and the constraints and risks associated with radiological scans prompt the need for accurate non-invasive means to monitor minimal residual disease (MRD) in solid tumors. In this study we describe MRD evaluation via profiling of patient-specific gene variants in cell free tumor DNA (i.e., ctMRD). We evaluate the feasibility of this approach for real time monitoring of tumor lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Paired analysis of patient plasma from ctDNA using a targeted approach, like molecular tag-based sequencing, may reveal concordant mutations with the tumor tissue that could be used for disease monitoring during follow-up. In a recent study that monitored patient-specific ctDNA across a diverse set of tumors, the authors found that for patients (n=40) with three or more longitudinal time points the patient-specific ctDNA had a correlation with tumor burden in 16/19 (85%) patients with partial response and overall in 27/40 (68%) patients 162 . On the other hand, use of cancer antigens only correlated with tumor burden in 19/40 (47.5%) patients, suggesting a lower utility than patient-specific ctDNA.…”
Section: B) Cell-free Tumor Dna In Liposarcomamentioning
confidence: 99%
“…Paired analysis of patient plasma from ctDNA using a targeted approach, like molecular tag-based sequencing, may reveal concordant mutations with the tumor tissue that could be used for disease monitoring during follow-up. In a recent study that monitored patient-specific ctDNA across a diverse set of tumors, the authors found that for patients (n=40) with three or more longitudinal time points the patient-specific ctDNA had a correlation with tumor burden in 16/19 (85%) patients with partial response and overall in 27/40 (68%) patients 162 . On the other hand, use of cancer antigens only correlated with tumor burden in 19/40 (47.5%) patients, suggesting a lower utility than patient-specific ctDNA.…”
Section: B) Cell-free Tumor Dna In Liposarcomamentioning
confidence: 99%